Mycosis Fungoides Preceding Pityriasis Lichenoides et Varioliformis Acuta by Twelve Years in a Pediatric Patient. (December 2021) - Lowe, Erin; Jacobsen, Jeffrey R.; Taylor, Steve; Miller, Richard; Price, Harper N.; Andrews, Israel D.
Abstract : Abstract: A 15-year-old boy presented to the pediatric dermatology department with long-standing patch stage CD8+ mycosis fungoides and subsequent development of recurrent pityriasis lichenoides et varioliformis acuta eruptions. There have been rare reports of patients with chronic, recalcitrant pityriasis lichenoides developing mycosis fungoides, but we believe this to be the second case of mycosis fungoides preceding a diagnosis of pityriasis lichenoides, and the first case reported in the pediatric population.